DEVELOPMENT AND USE OF COMPOSITIONS FROM PRODUCTS OF DEEP PROCESSING OF SECONDARY MEAT RAW MATERIALS - Marianna I. Kremenevskaya; Ruslan V. Dobryagin; Vladimir V. Bogomolov; Sergey I. Snarkiy (Теория и практика переработки мяса)
The development of protein ingredients based on the composites from secondary collagen-containing meat raw materials and obtained by the methods of deep processing attracts increasing attention of specialists.In the presented work, the composite and mass composition of the protein ingredient from hydrolysates of beef hide split, pork skin and blood plasma in a ratio of 45:45:10 was established. The improved amino acid composition of the protein ingredient due to addition of dry blood plasma suggests an increased biological and nutritional value of the developed product. Addition of up to 15 % of the protein ingredient instead of beef in the technology of minced semi-prepared products improves the rheological and organoleptic characteristics of the finished product.